2020
DOI: 10.3390/molecules25051141
|View full text |Cite
|
Sign up to set email alerts
|

High-Valent NiIII and NiIV Species Relevant to C–C and C–Heteroatom Cross-Coupling Reactions: State of the Art

Abstract: Ni catalysis constitutes an active research arena with notable applications in diverse fields. By analogy with its parent element palladium, Ni catalysts provide an appealing entry to build molecular complexity via cross-coupling reactions. While Pd catalysts typically involve a M0/MII redox scenario, in the case of Ni congeners the mechanistic elucidation becomes more challenging due to their innate properties (like enhanced reactivity, propensity to undergo single electron transformations vs. 2e− redox seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 145 publications
0
23
0
Order By: Relevance
“…Successful formation of C­(sp 3 )–O–C­(sp 3 ) bonds using N -fluoropyridinium reagents posed the question of what is the exact nature of the high-valent Ni species involved in the process. On the basis of the CV results for 2b (Figure ) together with the oxidation results using Fc + , O 2 , and 4CzIPN photocatalyst (Scheme ), it is evident that access to Ni III species is facile; yet, cationic Ni III are not capable of C–O bond formation due to fast elimination side reactions. It is important to point out that owing to the extremely fast reaction rates for C–O bond formation, mechanistic investigations on this particular system pose an experimental challenge.…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Successful formation of C­(sp 3 )–O–C­(sp 3 ) bonds using N -fluoropyridinium reagents posed the question of what is the exact nature of the high-valent Ni species involved in the process. On the basis of the CV results for 2b (Figure ) together with the oxidation results using Fc + , O 2 , and 4CzIPN photocatalyst (Scheme ), it is evident that access to Ni III species is facile; yet, cationic Ni III are not capable of C–O bond formation due to fast elimination side reactions. It is important to point out that owing to the extremely fast reaction rates for C–O bond formation, mechanistic investigations on this particular system pose an experimental challenge.…”
Section: Results and Discussionmentioning
confidence: 98%
“…With these results in hand, we addressed such a defying and elusive reductive elimination. It was clear that other oxidants that enable access to high-valent Ni species should be scrutinized . When I 2 was replaced by Umemoto’s reagent ( S -(trifluoromethyl)­dibenzothiophenium triflate, TDTT, 10a ), a low yield of 2b was observed (10%).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Regarding the review-type contributions to this Special Issue, Guo and co-workers present a general overview of the use of cyclic carbonates and carbamates as starting building blocks in organic synthesis via transition-metal-catalyzed decarboxylation for the synthesis of different heteroaromatic organic architectures, ranging from chiral tetrahydroquinolines, functionalized indoles and furanbenzodihydropyran derivatives to chiral 3-indolin malononitriles, among others [10]. Finally, Dr. Noel Nebra reports an outstanding and complete review of high-valent Ni(III) and Ni(IV) organometallic species [11], which is nowadays a hot topic area in the field of transition-metal-catalyzed formation of C-C and C-Heteroatom bonds. Moreover, the author also presents in his review the actual state of the art on the different mechanistic proposals to support the catalytic activity of the aforementioned high-valent Ni(III) and Ni(IV) organometallic species.…”
Section: Figurementioning
confidence: 99%
“…[5] These catalytic reactions are often proposed to proceed via high valent Ni III /Ni IV intermediates. [6] In the last few years,s everal reports have suggested that complexes that have access to high valent oxidation states of nickel can end up being competent catalysts in CÀO, [7] CÀC [8] bond formation, and CÀHb ond functionalization. [9] However, ag eneral approach for the accessibility/formation of high valent nickel complexes is still lacking due to their low stability.…”
Section: Introductionmentioning
confidence: 99%